(3deMI aj JGQjN OhdI GdTQaGA HGdeZQHs - (3CHhRjO GdaGSj , YHO GdQMef Hf YHO GdbGOQ Hf Ydj Hf CHj GdeMGSf jhSa GdaGSj,J (B1096 (3g` s
(3ChdgG (B:s
(3GdMeO ddg , PcQ OhdI GdTQaGA, LGA GhGFdge OQYI aGTbQhG HgG HYO ChGFd GdeGFI GdKGefI s
(3BNQgG (B:s
(3haj efJUa LeGOj GdKGfjI YGe (B1030 (3HYK YHOGddg ddbHGFd hGdMeO ddg QH GdYGdejf Gg` ef NW GdTjN GdEeGe CHj RjO SjOj YHOGdQMef GdaGSj QMe Gddg GdLejY HaVdg hQMeJg Bejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B145s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B695 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B360 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B56) s
Keywords: (3GdJGQjNs